Surfactant Proteins A and D Enhance Pulmonary Clearance of Pseudomonas aeruginosa - Giannoni, Eric (American Thoracic Society, 2006)
Surfactant protein (SP)-A and SP-D, members of the collectin family, are involved in innate host defenses against various bacterial and viral pathogens. In this study, we asked whether SP-A and SP-D enhance clearance of a nonmucoid strain of Pseudomonas aeruginosa from the lungs. We infected mice deficient in SP-A (SP-A−/−), SP-D (SP-D−/−) and both pulmonary collectins (SP-AD−/−) by intratracheal administration of P. aeruginosa. Six hours after infection, bacterial counts were significantly higher in SP-A−/−, SP-D−/−, and SP-AD−/− compared with wild-type (WT) mice. Forty-eight hours after infection, bacterial counts were significantly higher in SP-A−/− mice compared with WT mice and in SP-AD−/− mice compared with WT, SP-A−/−, and SP-D−/− mice. Phagocytosis of the bacteria by alveolar macrophages was decreased in SP-A−/− and SP-D−/− mice. Levels of macrophage inflammatory peptide–2 and IL-6 were more elevated in the lungs of SP-D and SP-AD−/− mice compared with WT mice. There was more infiltration by neutrophils in the lungs of SP-D−/− compared with WT and SP-A−/− mice 48 h after infection. This study shows that SP-A and SP-D enhance pulmonary clearance of P. aeruginosa by stimulating phagocytosis by alveolar macrophages and by modulating the inflammatory response in the lungs. These findings also show that the functions of SP-A and SP-D are not completely redundant in vivo.